Efforts to Moderate Islamic Law Understanding through Hadith Studies in Aceh and West Sumatra Mosques - M.Jakfar, Tarmizi; Maizuddin; A. Muchsin, Misri; Sri Chalida; Nadhilah Filzah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
This study aims to portray mosques' contribution in Islamic study gatherings; examine preferred subjects of the gathering in Acehnese and West Sumatra mosques; and acquire a moderate understanding of hadith and Islamic law at the locus. It uses an empirical legal method combined with Weber's theory of social action. Data were collected through in-depth interviews, observation, and document studies. The study found that the mosque has long been playing a big role in facilitating pengajian (Islamic study gathering), including that of Islamic law and hadith subjects. However, the intensity or frequency is still relatively low in both Aceh and West Sumatra, so hadith studies are still rarely held in these two regions. The role of mosques as a place to gain a moderate understanding of Islamic law from the study of hadith study gathering (pengajian hadith) is important even though it is not yet optimal. In Weber's perspective, a person's social actions will be influenced by an understanding one considers correct, which will then become a religious practice. A moderate understanding of Islamic law will emerge then lead to harmony and tranquility in society.